Pentahelix Model to Create Shared Value in Empowering the People of Winong Village, Gempol District, Pasuruan Regency - Aminullah Aminullah; Any Urwatul Wusko (Global Review of Tourism and Social Sciences, 2025)
This study addresses the gap in understanding how such policies influence local economies, specifically in Winong Village. The research introduces a novel application of the pentahelix model, focusing on private actors' role in fostering "Creating Shared Value" (CSV), an evolution of Corporate Social Responsibility (CSR). Unlike traditional CSR initiatives, CSV emphasizes collaborative value creation that benefits both businesses and communities. This qualitative descriptive research aims to explore and develop collaboration among pentahelix actors—government, private sector, academia, media, and society—who play pivotal roles in economic development. Through in-depth analysis of social realities, the study identifies the unique characteristics and potential of the pentahelix model in enhancing community economic empowerment. Field findings reveal that the pentahelix model, integrated with the CSV approach, effectively supports sustainable economic growth in Winong Village. These results highlight the importance of fostering public-private partnerships and innovative strategies for post-pandemic economic recovery, offering valuable insights for broader applications in similar contexts.